A method of preparing a water-dispersible graphene nanoplatelet and uses thereof - Lim, Hong Ngee (2021)
The present invention relates to a method (100) of preparing a water-dispersible graphene nanoplatelet comprises the steps of adding a graphene nanoplatelet and an active material into a container, grinding and mixing the graphene nanoplatelet and the active material for 1 to 15 min to obtain a mixture and heating the mixture via microwave at medium energy in the range of 80 to 560 W for 1 to 15 min to obtain the water-dispersible graphene nanoplatelet. More particularly, the active material is a mixture comprising a sulfonate structure having an aromatic or a non-aromatic ring, a polymer having formaldehyde, a salt and a solvent. Further, the present invention also relates to an application of the water-dispersible graphene nanoplatelet in preparing a composite with a hydrophilic polymer including a rubber, a synthetic polymer and a natural polymer.